DEBRIS-MANTLED RECTILINEAR SLOPES IN THE WESTERN SØR RONDANE MOUNTAINS, EAST ANTARCTICA - イワタ, シュウジ; IWATA, Shuji (National Institute of Polar Research, 1987)
P(論文) In the western part of the Sør Rondane Mountains, slopes in the ice-free area are classified into the following seven categories : cliff or free face, ice-smoothed steep slope, areal-scouring gentle topography, till-covered steep slope, debris-and/or till-covered areal-scouring gentle topography, debris-mantled rectilinear slope, and talus slope. Among them the last two categories are well developed. Debris-mantled rectilinear slopes especially occur on the north-facing slopes in gneiss rock areas. They are characterized by smooth surface, rectilinear profiles with angles of 29°-37°, and thin debris-mantled surface. They are thought to be a kind of the Richter denudation-slope, but intensive joints occurring in the gneiss bedrock control slope configurations. departmental bulletin paper